Pembinaan Peningkatan Kemampuan Berbahasa Arab Melalui Metode Muhawaroh (Dialog) Santri TPQ Al-Akidah Telage Ngembeng, Kabupaten Lombok Barat - Lalu Ahmad Didik Meiliyadi; Akmal Mauladi; Muhammad Sakaki; Aizyra Amalya Garnis; Rahmatdun Hariadi (Prodi Tadris IPA Biologi UIN Mataram, 2023)
Community service has been carried out in the form of community service such as teaching and learning activities held by KKP UIN Mataram students at TPQ Al-Akidah, TelageNgembeng Hamlet, Nyurlembang Village, Narmada District. Through this activity students are expected to experience an increase in understanding and recognizing Arabic. The method used in this activity is Participatory Action Research (PAR). This activity was carried out in 4 stages, namely (a) preparation, (b) socialization, (c) implementation and finally (d) evaluation and reflection. Service activities have been carried out with good results. Based on the results of the activity evaluation, it shows that most students are enthusiastic in carrying out PhET-based virtual practicum with points 3.4 which shows that students are very enthusiastic. While the lowest point is in the time aspect with 2.6 points. The time for implementing the activity was felt to be very limited so that there were still students who felt they did not understand Arabic